Soil health and quality concept in agricultural extension and soil science : an assessment of topsoil conditions in a long term vineyard soil management trail in Robertson, South Africa - Mathys, Ilse Lois (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Soil Science))--University of Stellenbosch, 2011.